Aprendizaje situado: género y entornos de aprendizaje (2013)
This paper reports the main findings of an exploration of the gender condition (masculine-feminine) with respect to the possible associations students make between learning contents and learning scenarios. Participants were 298 high school students from public schools in Bogotá, Colombia. They answered a questionnaire composed of 31 items that asked for the frequency with which they used certain scenarios to gain access to certain learning contents. Results points out the masculine preference for virtual spaces to look for information of different sorts while women use this scenario mainly for social issues. To gain access to other types of knowledge (different from social behavior) women prefer their homes and, in general, inner, personalized spaces. In contrast, men show less apprehension with respect to exterior public scenarios such as libraries and streets.